Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/emm.2017.128
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cellular balance of Rps3 mono-ubiquitination by both Hel2 E3 ligase and Ubp3 deubiquitinase regulates protein quality control

Abstract: When a ribosome complex is stalled during the translation elongation process in eukaryotes, the mono-ubiquitination of Rps3 has recently been shown to be critical to ribosome quality control. We have discovered that the regulatory role of Rps3 mono-ubiquitination is controlled by a deubiquitinase. We also showed that an autophagic signal appears to be coupled to the mono-ubiquitination of Rps3p through the entrance of Ubp3p into the autophagosome in yeasts. The mono-ubiquitination of the Rps3 protein is tightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…Because carbohydrate transporters are plasma membrane proteins, this finding is consistent with previous studies linking down-regulation of membrane receptors to monoubiquitination-mediated endocytosis [5]. The stability of ribosomal and proteasomal subunits is also regulated by monoubiquitination [6]. Multi-monoubiquitination could also act as a degradation signal [7].…”
Section: Monoubiquitination In Protein Functionsupporting
confidence: 89%
“…Because carbohydrate transporters are plasma membrane proteins, this finding is consistent with previous studies linking down-regulation of membrane receptors to monoubiquitination-mediated endocytosis [5]. The stability of ribosomal and proteasomal subunits is also regulated by monoubiquitination [6]. Multi-monoubiquitination could also act as a degradation signal [7].…”
Section: Monoubiquitination In Protein Functionsupporting
confidence: 89%
“…Previous studies showed that monoubiquitination of RPS3 by Asc1 (RACK1 in mammals) or Hel2 is required for ribosome-associated quality control [ 19 , 31 ] but does not cause proteasomal degradation of RPS3. Although treatment with the HSP90 inhibitor elicited UPS-dependent degradation of RPS3, recruiting HSP70 [ 18 ], the identity of the E3 ligase responsible for RPS3 degradation and its biological significance have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…USP10 also plays a critical role in protein quality control by regulating the monoubiquitination of Rsp3 (30). Misfolded proteins, a potential intracellular toxic species, are recognized by chaperones and eliminated from cellular environment broadly by the ubiquitin-proteasome system.…”
Section: Usp10mentioning
confidence: 99%
“…It has previously been reported that ubiquitination of ribosomal proteins regulates the ribosomal quality control (RQC) activity. During active translation, Rsp3 is monoubiquitinated by the Hel3p/RNF123 E3 ligase (30). It is well established that the temporal stalling of the ribosome during translation activates RQC pathways.…”
Section: Usp10mentioning
confidence: 99%